Audience Meaning of Teenage Life Delinquency Through Euphoria Series as Mass Media Effect - Alfonso Harrison; Theodora Jessica; Cecilia Francessa (Jurnal Komunikasi dan Bisnis, 2025)
This research aims to find out the meaning that emerges in the audience about the reality of adolescent life as a result of mass media, in this case, the soap opera Euphoria, which is watched with intense viewing behavior. This study uses a constructivist paradigm and a qualitative approach. This research chooses Generation Z teenagers, aged 18 to 22 years, as subjects. Data collection was carried out by interviewing informants, whose results were compared with semiotic analysis of the Euphoria series as the object of research. data was obtained that informants, as heavy viewers who watch films intensively, find teenage life scary, as depicted in Euphoria. Informants with their own life experiences tend to want to imitate the characters in Euphoria. This illustrates the concept of resonance working in forming the effects of mass media, namely, cognitive and affective. In addition, through the Euphoria series, the media displays the diversity of behavior in the culture of today's teenage life, and informants also show inclusive acceptance of cultural behavior that tends to be considered difficult to accept by the conventional culture of Indonesian society. The conclusion is that the mainstreaming and resonance concepts are discovered in informants, therefore, these two concepts might trigger the mass communication effects that are cognitive, affective, and behavioral in the audience of the show.